The Paradigm of Islamic Education Philosophy in the Development of Religious Moderation - M. Bayu Sandhya; Mhd. Habibu Rahman; Tondy Jimmy Pasaribu (International Journal of Society and Law, 2025)
This study aims to analyze the paradigm of Islamic education philosophy in the development of religious moderation as a conceptual and praxis foundation in building inclusive, tolerant, and civilized religious attitudes in the midst of a multicultural society. The paradigm of Islamic educational philosophy studied includes ontological, epistemological, and axiological dimensions derived from the Qur'an, Sunnah, as well as the thoughts of Muslim philosophers and scholars, which place human beings as beings of nature, reason, and morality. This study uses a qualitative approach with the type of library research through a critical analysis of classical and contemporary literature that is relevant to the concept of Islamic education and religious moderation. The results of the study show that the paradigm of Islamic education philosophy essentially contains the principles of tawasuth (moderate), tawazun (balanced), tasamuh (tolerant), i'tidal (fair), and musawah (egalitarian) which can be integrated into the curriculum, learning process, and academic culture of educational institutions. Epistemologically, the integration between revelation and reason is an important foundation in building a moderate mindset that is dialogical and contextual, while axiologically, universal human values are the main orientation in the formation of students' characters. Thus, the paradigm of Islamic education philosophy has strategic relevance in strengthening religious moderation as a preventive effort against radicalism, intolerance, and social polarization, as well as as the foundation for the development of a harmonious and sustainable civilization.